Topological Encoded Vector Beams for Monitoring Amyloid‐Lipid Interactions in Microcavity. Issue 12 (2nd May 2021) - Gong, Chaoyang; Qiao, Zhen; Yuan, Zhiyi; Huang, Shih‐Hsiu; Wang, Wenjie; Wu, Pin Chieh; Chen, Yu‐Cheng
Abstract: Lasers are the pillars of modern photonics and sensing. Recent advances in microlasers have demonstrated its extraordinary lasing characteristics suitable for biosensing. However, most lasers utilized lasing spectrum as a detection signal, which can hardly detect or characterize nanoscale structural changes in microcavity. Here the concept of amplified structured light‐molecule interactions is introduced to monitor tiny bio‐structural changes in a microcavity. Biomimetic liquid crystal droplets with self‐assembled lipid monolayers are sandwiched in a Fabry–Pérot cavity, where subtle protein‐lipid membrane interactions trigger the topological transformation of output vector beams. By exploiting Amyloid β (A β )‐lipid membrane interactions as a proof‐of‐concept, it is demonstrated that vector laser beams can be viewed as a topology of complex laser modes and polarization states. The concept of topological‐encoded laser barcodes is therefore developed to reveal dynamic changes of laser modes and A β ‐lipid interactions with different A β  assembly structures. The findings demonstrate that the topology of vector beams represents significant features of intracavity nano‐structural dynamics resulted from structured light‐molecule interactions. Abstract : The potential of vector laser beams is demonstrated to detect tiny bio‐structural changes in a microcavity through structured light‐molecule interactions. The topology of laser modes is converted into laser barcodes to reveal dynamic changes of amyloid‐lipid membrane interactions. Kinetic fingerprints of laser barcodes thus offer the potential for studying biophysical interactions in a wide range of biomedical applications.